On Seamus Heaney - Foster, R. F. (Robert Fitzroy), 1949- (Writers on writers., 2020)
"Seamus Heaney was the leading Irish poet of the second half of the twentieth century, and, after W. B. Yeats, arguably the most significant poet in the history of Irish literature. When he died in 2013 the public reaction in Ireland was extraordinary, and the outpouring of feeling decisively demonstrated that he occupied an exceptional place in national life. The words of his last message to his wife, 'Noli timere', 'Don't be afraid', appeared over and over again on social media, while key phrases from favourite poems became and have remained canonical. In this short book, conceived for the Writers on Writers series, historian Roy Foster offers an extended and largley chronological reflection upon Heaney's life, work and historical context, from the poet's origins in Northern Ireland and the publication of Death of a Naturalist in 1966, through the explosive impact of his 1975 collection North, and then into his years as a 'world poet' and an Irish writer with a powerful influence on English literature generally. Foster considers virtually all of Heaney's major output, including later volumes such as The Spirit Level and Human Chain, as well as Heaney's translation of Beowulf and his renderings from Virgil. Throughout the book, Foster conveys something of Heaney's charismatic, expansive and subtle personality, as well as the impact of his work in both the USA and in Europe. Certain themes emerge throughout, such as the way Heaney maintained a deceptive simplicity throughout his writing career, his relations with classical literature and the poetry of dissidence in Eastern Europe, and the increasing presence of the unseen and even spiritual in his later work. Foster also highlights Heaney's importance as a critic and the largely unacknowledged ways in which his own trajectory echoed that of the life and work of Yeats. Though Heaney evaded direct comparisons with his Nobel-prizewinning predecessor, he personified the quality which he attributed to Yeats: 'the gift of establishing authority within a culture'. Both poets made a challenging and oblique use of autobiography and personal history in their work, and both sustained a very particular and sometimes contested relation to the life of their country. Foster shows us that Heaney, like Yeats, came to personify and express the Ireland of his time with unique force and resonance"--